Features of Clinical Presentation, Diagnosis and Treatment of Mycoplasmal Pneumonia in Children - Ye.I. Yulish; O.Ye. Chernyshova; A.A. Konyushevskaya; A.K. Talalayenko (Zaslavsky O.Yu., 2014)
This paper presents the features of clinical presentation, diagnostic methods, principles of rational treatment of mycoplasmal pneumonia in childhood.